"It's probably untrue, but it wouldn't matter anyway": ei kai Conditions in the Greek New Testament - Proctor, Mark ca. 21. Jh. (Neotestamentica, 2019)
This article examines the structure and interpretive significance of the Greek New Testament's twenty-two εἰ καί conditions. It seeks to demonstrate that the presence of an adverbial καί at the head of a first class condition effectively signals that neither its satisfaction nor its dissatisfaction nullifies the claim in the apodosis. While the protasis of an εἰ καί condition normally presents a contrary-to-fact notion, such need not always be the case. What seems clear, however, is that the New Testament writers deploy the εἰ καί structure in part to indicate that they would concede the truth of the protasis only with reluctance. Such is in keeping with the normal additive effect that adverbial καί has on the meaning of whatever discourse unit it modifies. This understanding of the meaning of εἰ καί conditions differs greatly from the opinion of those who treat their protases like concessive clauses. Hence, what a second class condition does to deny the truth of its apodosis (and, by extension, also its protasis), an εἰ καί condition does instead to affirm the same while casting doubt on the protasis. Approaching the Greek New Testament's examples of εἰ καί conditions with such an understanding generates a number of potential ways to improve the New Revised Standard Version.